Resistance of seagrass habitats to ocean acidification via altered interactions in a tri-trophic chain - Martínez-Crego B; Vizzini S; Califano G; Massa-Gallucci A; Andolina C; Gambi MC; Santos R (Scientific Reports, 2020)
Despite the wide knowledge about prevalent effects of ocean acidification on single species, the consequences on species interactions that may promote or prevent habitat shifts are still poorly understood. Using natural CO2 vents, we investigated changes in a key tri-trophic chain embedded within all its natural complexity in seagrass systems. We found that seagrass habitats remain stable at vents despite the changes in their tri-trophic components. Under high pCO2, the feeding of a key herbivore (sea urchin) on a less palatable seagrass and its associated epiphytes decreased, whereas the feeding on higher-palatable green algae increased. We also observed a doubled density of a predatory wrasse under acidified conditions. Bottom-up CO2 effects interact with top-down control by predators to maintain the abundance of sea urchin populations under ambient and acidified conditions. The weakened urchin herbivory on a seagrass that was subjected to an intense fish herbivory at vents compensates the overall herbivory pressure on the habitat-forming seagrass. Overall plasticity of the studied system components may contribute to prevent habitat loss and to stabilize the system under acidified conditions. Thus, preserving the network of species interactions in seagrass ecosystems may help to minimize the impacts of ocean acidification in near-future oceans.